Strategies to improve academic motivation among nursing students : Strategije poboljšanja akademske motivacije među studentima sestrinstva - Cilar, Leona (Array, 2020)
Introduction: Academic motivation of nursing students is a broad concept that has an impact on academic success, education and personal satisfaction. Motivation to study often decreases with years of study, thus it is important to find out effective strategies for motivating nursing students. Methods: A scoping review was conducted in 2020 to determine the scope and body of literature on strategies for motivating nursing students. A literature search was performed in four international databases (PubMed, Medline, Science-Direct and Google Scholar) using inclusion and exclusion criteria. The literature search and analysis are shown using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. Results: Out of 560 identified studies, a total of 14 studies were included in the final analysis. Most of the identified studies were quasi-experimental studies (n=8; 57.14 %) exploring the effectiveness of existing strategy. Strategies that showed positive effects in raising nursing student’s academic motivation are gamification, mobile applications, forums, problem-based learning, and other specific strategies. Discussion: It is evident that new strategies have positive impact on nursing student’s academic motivation. Nevertheless, there is a need for further research and testing before the process of implementing those strategies in specific learning environment. Conclusion: There is a constant need for education of future nurses. To ensure appropriate nurses’ knowledge and skills, academic motivation is needed.